(untitled) (Jurnal Kesehatan Komunitas, 2022)
Stunting is not considered a serious problem that needs to be followed up immediately. Mothers with children who suffer from stunting have wrong knowledge. Efforts to increase the knowledge of mothers of infants and toddlers about stunting can be done by using integrating card media. The purpose of this study was to see the effect of promotive efforts to increase the knowledge of mothers under five about stunting with media integrating cards at Posyandu Kenanga 3 Puskesmas Kebon IX in 2021. This research is a Pre Experiment with a one group design research design. This research was conducted from March 2021 to September 2021 at Posyandu Kenanga 3 Puskesmas Kebon IX. The population in this study were 55 mothers of children under five at Posyandu Kenanga 3 Puskesmas Kebon IX. The sample in this study were 36 people who were taken by accidental sampling technique. Collecting data using a questionnaire. Data were analyzed by univariate and bivariate using paired sample T test. The results of this study showed that the knowledge of mothers after being treated using media integrating cards about stunting mostly had poor knowledge, namely 23 people (63.9%) and knowledge of mothers after being given treatment mostly had good knowledge, namely 31 people (86, 1%). There is an effect of promotive efforts to increase the knowledge of mothers under five about stunting with media integrating cards with a p value of 0.000 <0.05. The results showed that promotive efforts using media integrating cards could increase knowledge about stunting. For this reason, it is expected to increase knowledge in the field of health sciences and insight into health promotion using media integrating cards and increase knowledge in counseling about stunting